Oxford e-Research 08 - Oxford Internet Institute (Oxford Internet Institute, 2008)
This multi-disciplinary, international conference on e-Research will be held at the University of Oxford from 11-13 September 2008. It is being organized by a consortium of research projects in association with the journal Information Communication and Society (iCS). The conference seeks to stimulate and inform multi-disciplinary research on the development, use and implications of information and communication technologies (ICTs), like the Internet, in shaping research across the disciplines. It will bring together research from key e-Research projects from around the world examining the role of the Internet, Web and the Grid in research. The conference seeks to facilitate scholarly communication and publication on this topic, and help foster a broader public understanding of the significance of this area to the sciences and humanities as well as to the public at large.